The role of autophagy in skeletal muscle homeostasis - Tomonori Ogata (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Autophagy is a process in which lysosomes participate in the degradation of cellular proteins and organelles, and is essential for cell survival. Recent studies of autophagy have focused on its role in skeletal muscle homeostasis. Autophagic flux in skeletal muscle is induced not only by atrophic stimuli such as fasting and denervation, but also by physical exercise. Excessive activation of autophagy promotes the progression of muscle atrophy. In contrast, impaired or deficient autophagy appears to promote muscle weakness, myopathy, and age-related muscle atrophy due to the accumulation of denatured proteins and damaged organelles. The induction of autophagy during exercise is believed to play a role in physiological adaptations to exercise, such as increased oxidative capacity and insulin sensitivity. Thus, it is important for skeletal muscle homeostasis to appropriately regulate autophagy.